Delayed Mental Nerve Neuralgia following Chin Augmentation - Ineke Wever; Sang Hwang; Sim Choroomi; William Mooney (Case Reports in Otolaryngology)
This paper describes a case of mental nerve neuralgia following a traumatic dislodgement of a chin implant ten months after surgery. Our case is unusual, both in the specific complication and the patients' atypical representation—delayed and initially without mention of trauma. To the authors' knowledge, this case has not been reported previously in the literature. We review the complications of chin augmentation and the techniques for fixation and discuss implications for the preoperative disclosure with patients.